A Comparison between office and other ambulatory practices: Analysis from the National Anesthesia Clinical Outcomes Registry. Issue 4 (April 2016) - Jani, Samir R.; Shapiro, Fred E.; Gabriel, Rodney A.; Kordylewski, Hubert; Dutton, Richard P.; Urman, Richard D.
Abstract : Ambulatory and office‐based surgery is expanding rapidly. While growth continues, there are lingering patient safety concerns. To this end, the American Society of Anesthesiologists (ASA) created the Anesthesia Quality Institute (AQI), which collected patient and procedural characteristics on 23 341 130 anesthetics from all health care settings from 2010 to 2014. Of these, 179 618 office and 4 627 379 ambulatory cases were isolated and compared. Our findings show that although both settings are often grouped together, there are statistically significant differences in patient demographics, procedure types, and reported adverse events. Among these reports, inadequate postoperative pain control and nausea/vomiting are the most common issue. More serious events such as death, cardiac arrest, and vision loss occurred but were rare.